Levying evidence of the impact of Triphala in the mildly constipated human colon microbiota - Elizabeth Goya-Jorge; Pauline Bondue; Irma Gonza; Samiha Boutaleb; Caroline Douny; Marie-Louise Scippo; Joël Pincemail; Patrice Chiap; Jeoffrey Christyn de Ribaucourt; Fabienne Crahay; Véronique Delcenserie (Journal of Functional Foods)
Triphala is a wildly used nutritional and phytotherapeutic formulation combining three dry fruits (Terminalia bellirica, Terminalia chebula and Emblica officinalis). Despite its long-standing use to treat gastrointestinal discomfort, there is limited understanding of Triphala's effects on gut microbiota, especially among individuals with mild constipation. Thus, this study aimed to investigate Triphala's impact on the constipated human colon microbiota. A short-term (72 h) static configuration of the in vitro Simulator of the Human Intestinal Microbial Ecosystem (SHIME®) system was used to study the fermentation process of a standardized extract of Triphala in the gut microbiota. Chromatographic and enzymatic methods were used to analyze the microbe-derived metabolic production. Potential herb-human host interactions were assessed using in vitro cell-based methods. Triphala extract increased Akkermansia muciniphila but decreased Bifidobacterium spp. in the simulated colon microbiota. Metabolic profiling of Triphala treatment showed increased phenolic species and antioxidant potential and reduced ammonia, valeric, isovaleric, and isobutyric acids during fermentation, potentially benefiting intestinal health, especially in contexts of constipation. Fermentation metabolites enhanced transepithelial electrical resistance in a human epithelium model and inhibited aryl hydrocarbon receptor (AhR) transcriptional activity. Triphala's polyphenols likely cause this AhR antagonism. Overall, these findings state some potential explanations for the usefulness of Triphala as a natural remedy for gastrointestinal diseases. However, it also raises concerns about some harmful effects of Triphala in the gut microbial ecosystem of people suffering from mild constipation.